Identification of Leading Commodity Areas in the Agricultural Sector Based on Historical Data and Land Suitability - Delvi Yanti; Eri Stiyanto; Nika Rahma Yanti; Choiruddin Batubara; Ferdian Ariyadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
In determining the utilization of the area, many government regulations have been made from the Central, Provincial, and Regional levels using a production data approach. However, it is getting different results with the same slice. The purpose of the study is to identify areas and determine priority agricultural commodities for food crops, horticulture, and plantation groups in Pasaman Regency. Analytical techniques used in Pasaman Regency are LQ analysis, shift share (SS) analysis, and field observation with a stakeholder approach. Based on the research, it is found that LQ and SS were able to determine the leading commodities of food crops, horticulture, and plantations in Pasaman Regency. The main food crop is corn, with the central development area in Tigo Nagari District. The superior horticultural crops and their development areas are chilies in Panti District and mangoes in Mapat Tunggul. The main plantation crop is rubber in a central development location in South Rao District. Keywords: Featured commodities; Historical data; Production; Land suitability; Pasaman